1985
DOI: 10.1029/rs020i006p01349
|View full text |Cite
|
Sign up to set email alerts
|

Altitude dependence of vertical velocity spectra observed by VHF radar

Abstract: Vertical velocity data observed by SOUSY VHF radar from May 29 to June 2, 1978, are systematically analyzed. The altitude dependences of frequency spectra and wave number spectra are presented, and their physical implications are given on the basis of existing theoretical models. In this paper we will present the results of our analysis of both the frequency and wave number spectra of vertical velocity over 105 consecutive height ranges from 0.9 km to 16.5 km. We will then attempt to interpret the data using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
(1 reference statement)
6
11
0
Order By: Relevance
“…These "break points" are at ∼ 9 km for active conditions and ∼ 10.5 km for quiet conditions, which are close to the tropopause heights. A similar height dependence of spectral slopes was also reported by previous studies (e.g., Kuo et al, 1985;Larsen et al, 1987). When active and quiet periods are considered together (i.e., the whole data set is analyzed despite the background wind conditions), the so-called "general" spectra of vertical velocity are derived and reveal intermediate slopes compared with those under active or quiet conditions.…”
Section: Resultssupporting
confidence: 56%
“…These "break points" are at ∼ 9 km for active conditions and ∼ 10.5 km for quiet conditions, which are close to the tropopause heights. A similar height dependence of spectral slopes was also reported by previous studies (e.g., Kuo et al, 1985;Larsen et al, 1987). When active and quiet periods are considered together (i.e., the whole data set is analyzed despite the background wind conditions), the so-called "general" spectra of vertical velocity are derived and reveal intermediate slopes compared with those under active or quiet conditions.…”
Section: Resultssupporting
confidence: 56%
“…Because horizontal velocities can approach and even exceed 100 m/s, pointing accuracies of a few tenths of a degree or a few mrad are required to insure that horizontal contamination does not exceed a few tenths of m/s. Among the few reported measurements of vertical wind profiles and their spectra are the papers of Kuo et al [ 1985], Larsen et al [ 1986 Copyright 1995 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…The ST-radar studies of Kuo et al (1985) measured the slopes of vertical-velocity spectra to be near A1.7 in the middle troposphere and near A0.34 in the lower stratosphere. Larsen et al (1987) reported slopes near A1.3 for troposphere/lower-stratosphere data and Sidi et al (1988) reported a spectral slope of A1.8 for the lower stratosphere based on a high-resolution balloon measurement.…”
Section: Vertical-wave Number Spectramentioning
confidence: 99%